Soft X‐Ray Magnetic Circular Dichroism of Vanadium in the Metal–Insulator Two‐Phase Region of Paramagnetic V2O3 Doped with 1.1% Chromium. Issue 3 (4th November 2019) - Schmitz, Detlef; Schmitz-Antoniak, Carolin; Radu, Florin; Ryll, Hanjo; Luo, Chen; Bhandary, Sumanta; Biermann, Silke; Siemensmeyer, Konrad; Wende, Heiko; Ivanov, Sergey; Eriksson, Olle
Abstract : V2 O3 doped with 1.1% Cr is investigated at its isostructural correlation‐driven metal–insulator transition near room temperature in its paramagnetic state with X‐ray magnetic circular dichroism (XMCD) spectroscopy in external magnetic fields. A relative XMCD amplitude of about 2 permille is observed at the L 2, 3 absorption edges of vanadium as expected for magnetic moment per mass values of the order of 1 J T −1  kg −1 from magnetometry and the literature. Across the metal–insulator transition, the vanadium XMCD spectral shape significantly changes. According to atomic multiplet simulations, these changes are due to a changing orbital occupation indicating a changing phase composition. According to estimates used in this study, the dipole moment of the spin density distribution 7 ⟨ T z ⟩ in the bulk increases such that the effective vanadium spin moment increases by a few percent with temperature in the two‐phase region. Thereby, it partially compensates for the decrease in the relative XMCD amplitude due to a decreasing alignment of the paramagnetic moments. After a few minor temperature cycles, the sample is in a two‐phase state in which the XMCD and X‐ray linear dichroism spectra hardly depend on the temperature, and the specific electrical resistance is intermediate, showing only a weak sign of the metal–insulator transition. Abstract : Across the archetypal correlation‐driven metal–insulator transition of paramagnetic V2 O3 doped with 1.1% chromium, the orbital occupation and thus the dipole moment of the vanadium 3d spin density change, whereas the local spin and orbital moments are not affected. This is explored with element‐specific X‐ray magnetic circular dichroism spectroscopy and theory to elucidate the role of magnetism in the transition.